Factor analysis to determine the quality standards used in higher education: A case study in the Department of Total Quality Management - College of Technology Management - Baghdad - faysal naji nameq, (Iraqi Journal for Administrative Sciences, 2024)
The quality in higher education include the ( product ) which is the student level be equal the goal of population by using the good evaluation , good subjects , and good teaching methods , for this purpose I dependent on the most international requirement by design the questioners for students and the other for teachers in total quality management department / technical college of management baghdad . The first chapter devoted to the theoretical part of which was through the definition of quality and the type of accreditation and the idea of factor analysis, in chapter ii the practical side included the results of factor analysis for the student and teachers in this department , finally the research developed several results and presented the conclusions and suggestions and recommendations about it .